2015
DOI: 10.2967/jnumed.115.154443
|View full text |Cite
|
Sign up to set email alerts
|

Improving Cerebral Blood Flow Through Liposomal Delivery of Angiogenic Peptides: Potential of 18F-FDG PET Imaging in Ischemic Stroke Treatment

Abstract: Strategies to promote angiogenesis can benefit cerebral ischemia. We determined whether liposomal delivery of angiogenic peptides with a known biologic activity of vascular endothelial growth factor benefitted cerebral ischemia. Also, the study examined the potential of 18 F-FDG PET imaging in ischemic stroke treatment. Methods: Male Sprague-Dawley rats (n 5 40) underwent 40 min of middle cerebral artery occlusion. After 15 min of reperfusion, the rats (n 5 10) received angiogenic peptides incorporated into li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…The results support our hypothesis that PEGylated liposomes loaded with angiogenic peptides are efficacious for treating hindlimb ischemia, as evidenced by improved ischemic limb perfusion and increased expression of proteins related to angiogenesis. These findings are consistent with a previous study reporting the therapeutic effectiveness of liposomes loaded with angiogenic factors for treating cerebral ischemia (Hwang et al, 2015). That previous study showed the efficacy of a liposomal delivery system without surface PEG modification.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results support our hypothesis that PEGylated liposomes loaded with angiogenic peptides are efficacious for treating hindlimb ischemia, as evidenced by improved ischemic limb perfusion and increased expression of proteins related to angiogenesis. These findings are consistent with a previous study reporting the therapeutic effectiveness of liposomes loaded with angiogenic factors for treating cerebral ischemia (Hwang et al, 2015). That previous study showed the efficacy of a liposomal delivery system without surface PEG modification.…”
Section: Discussionsupporting
confidence: 93%
“…Liposomes encapsulated with angiogenic peptides were prepared as described previously with a slight modification (Hwang et al, 2015). A mixture of L-a-phosphatidylcholine (Egg PC), cholesterol, and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[Methoxy(polyethylene glycol)-2000] (DSPE-PEG2000) (the molar ratio of 50:40:10; Sigma-Aldrich, St. Louis, MO) was dissolved in chloroform/methanol (7:3; Duck San Pure Chemical, Gyunggi-do, South Korea).…”
Section: Preparation Of Pegylated Liposomes and Encapsulation With Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies reported in the literature suggest the efficacy of Hb liposomes in the treatment of stroke by enhancing the biodistribution of Hb liposomes within the ischemic area in the brain. 144,145,147,[160][161][162][163][164]167,171,191,193,194 In the same way, liposomes for the delivery of angiogenic peptides 140 and VEGF 157 to promote angiogenesis in ischemic tissue were developed, and both formulations effectively promoted vascular regeneration. 140,157 Over the years, many liposomal formulations have been developed for the treatment of stroke.…”
Section: Stroke or Cerebral Ischemiamentioning
confidence: 99%